2017
DOI: 10.1136/bmjdrc-2016-000365
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes patient’s perspective on Ramadan fasting: a qualitative study

Abstract: ObjectiveWe evaluated the beliefs, experience and diabetes management strategies of type 2 diabetes mellitus (T2DM) Muslim patients that chose to fast during Ramadan.Research design and methodsA semistructured focus group interview was conducted with 53 participants with T2DM. Participants were purposefully sampled and asked to share their perspective on Ramadan fasting. All interviews were audio recorded, transcribed verbatim and analyzed thematically.ResultsParticipants reported optimism towards fasting duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 27 publications
2
46
0
3
Order By: Relevance
“…The results from the group discussions echo previous findings related to the interface between formal care, the impact of the family and the community, beliefs and perceptions regarding fasting, religious influence, and managing blood glucose during Ramadan (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind, Kristiansen, Wittrup, & Nørgaard, ; Patel et al, ; Peterson et al, ). People with diabetes have been shown to fast despite their HCP advising against the practice (Chowdhury, Khan, Lasker, & Choudhary, ), and this was confirmed by the workshop participants when relating their experiences prior to DAFNE.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results from the group discussions echo previous findings related to the interface between formal care, the impact of the family and the community, beliefs and perceptions regarding fasting, religious influence, and managing blood glucose during Ramadan (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind, Kristiansen, Wittrup, & Nørgaard, ; Patel et al, ; Peterson et al, ). People with diabetes have been shown to fast despite their HCP advising against the practice (Chowdhury, Khan, Lasker, & Choudhary, ), and this was confirmed by the workshop participants when relating their experiences prior to DAFNE.…”
Section: Discussionsupporting
confidence: 78%
“…Although some participants discussed the negative aspects of fasting with diabetes, many had a positive outlook post‐DAFNE. Other studies have shown that some people with diabetes view Ramadan as an opportunity to manage their blood glucose, lose weight, and become closer to God, attributing this to the influence of religion on their beliefs and perceptions (Almansour et al, ; Gaborit et al, ; Lee et al, , ; Mygind et al, ; Patel et al, ; Peterson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During Ramadan, Muslims abstain from eating, drinking from sunrise to sunset. There have been reports that Ramadan results in altered sleep patterns, as well as changes in lifestyle habits . To date, there are no studies that have examined the effects of fasting on metabolic and sleep during Ramadan in individuals with type 2 diabetes mellitus (T2DM).…”
Section: Changes In Body Weight Metabolic Parameters At Baseline Andmentioning
confidence: 99%
“…kalitatif çalışmasında Tip 2 diyabetli bireylerin oruç tuttuklarında manevi açıdan (genel iyilik hali) kendilerini daha iyi hissettikleri ve aile bağlarını güçlendirdiklerini düşündükleri için oruç tuttuklarını ifade ettikleri belirtilmiştir. 21 Bu çalışmada Tip 2 diyabetli bireylerin yarıya yakının oruç tutmasının nedenleri olarak; %60,6'sında diyabet kronik komplikasyonlarının olmaması nedeniyle sağlıklarını iyi algılamaları ve dini görevlerini yerine getirmenin onlara huzur vermesi olduğu düşünülebilir (Tablo 1).…”
Section: Veri̇leri̇n Değerlendi̇ri̇lmesi̇unclassified